Efeito de biofertilizantes sobre o crescimento micelial e a germinação de esporos de alguns fungos fitopatogênicos - Tratch, Renato [UNESP]; Bettiol, Wagner [UNESP] (My University, 1997)
The biofertilizer was produced through anaerobic fermentation of cow manure adding milk, sugar, salts, cow liver parts and bone powder. After 73 days of fermentation it was evaluated the effect on micelial growth of Pythium aphanidermatum, Alternaria solani, Stemphylium solani, Septoria licopersici, Sclerotinia sclerotiorum, Botrytis cinerea, Rhizoctonia solani, Fusarium oxysporum f. sp. phaseoli and spores germination of B. cinerea, A. solani, Hemileia vastatrix and Coleosporium plumierae. In relation to micelial growth inhibition, the growth rate was calculated and it was found that, in general, concentrations over 10% caused a total inhibition of growth for the majority of fungi assayed. In case of spores germination, biofertilizer concentration over 20% has inhibited completely the germination of B. cinerea, over 10% inhibited A. solani, 5 and 1% of C. plumierae and H. vastatrix, respectively. Three different biofertilizers were also tested and one of them was less effective, which was the one produced with manure from confined cows opposed to the others produced with grazing cows.

Biofertilizantes produzidos a partir da fermentação anaeróbia de esterco bovino acrescido de leite, açúcar, sais, restos de fígado bovino e farinha de osso, por 73 dias, foram testados sobre o crescimento micelial de Pythium aphanidermatum, Alternaria solani, Stemphylium solani, Septoria licopersici, Sclerotinia sclerotiorum, Botrytis cinerea, Rhizoctonia solani, Fusarium oxysporum f. sp. phaseoli e sobre a germinação de conídios de B. cinerea, A. solani, Hemileia vastatrix e Coleosporium plumierae. Em relação à inibição do crescimento micelial verificou-se que, de modo geral, acima da concentração de 10% ocorreu completa inibição do crescimento desses fungos. Concentrações dos biofertilizantes acima de 20, 10, 5 e 1% inibiram totalmente a germinação de B. cinerea, A. solani, C. plumierae e H. vastatrix, respectivamente. Ao longo do estudo foram utilizados três diferentes biofertilizantes, tendo um deles apresentado comportamento diferenciado, isto é, menos efetivo. Na produção desse biofertilizante foi utilizado esterco originário de vaca leiteira confinada, enquanto nos demais de vaca leiteira submetida a pastoreio.
Effect of biofertilizers on micelial growth and spores germination of plant pathogenic fungi
Keywords: Biological control; Organic matter